CRYOPRESERVATION OF OOCYTES - Jadoon, Shandana; Adeel, Muhammad (Journal of Ayub Medical College Abbottabad, 2015)
Background: Various approaches have been utilized in attempting to cryopreserve oocytes, beginning with slow cooling and more recently the advent of technique of vitrification. Now it seems that oocyte cryopreservation is no longer an experimental technique and it is being increasingly utilized in clinics around the world. As successful outcome in oocyte cryopreservation can be assessed by survival through the freeze-thaw process, potential for fertilization, embryo development and dynamics of meiotic spindles. This study aimed to analyse these features in context of vitrification and slow freezing. Methods: In this laboratory based study, mature MII mouse oocytes from F1(C57BL6/J X CBA) mice (n=43) were divided randomly into two groups of equal numbers and were cryopreserved by slow freezing and by vitrification. Upon re-warming these oocytes were assessed for survival and for fertilization potential. Oocytes were fixed and stained to compare the effect of both protocols on spindle reassembly and chromosome configuration 10min, 1h and 3h after warming. Unfrozen oocytes were used as controls. Results: A greater number of vitrified oocytes survived cryopreservation than slow frozen oocytes (70.3% vs. 12.5%, p=0.024). After insemination, fertilization rates were higher for vitrified oocytes as compared to slow frozen oocytes (15.86% vs. 4.6%, p=0.046). Morphology of the meiotic spindle was found to be in a disorganized configuration in slow frozen oocytes at all-time points 10 mins, 1 h and 3h), whereas in vitrified oocytes the spindles were found to be aligned at all-time points. Chromosomes were seen to be displaced from equatorial region in both groups. Conclusion: Cryopreservation of mouse oocytes was conducted with greater success using vitrification, compared to slow freezing, with survival, fertilization, and spindle assembly more favourable to a successful outcome in this model. Keywords: Oocyte cryopreservation, Cryoprotectant, Vitrification, polarization microscopy (POLSCOPE), immuno-staining, fluorescent conjugated antibodies, slow freezing